Beyond geometric CAD system: implementation of STEP translator for multiple-views product modeller. (21st March 2007) - Song, Huijun; Eynard, Benoit; Roucoules, Lionel; Lafon, Pascal; , Sebastien Charles
A new kind of Computer-Aided Design (CAD) system is proposed to support the integration and collaboration in Concurrent Engineering (CE). The kernel of the system is the Co-operative Design Modeller (CoDeMo), which supports the multiple-views knowledge integration in the product definition. The enhancement of CoDeMo and CAx systems interoperability is required for achieving a consistent design support environment. This paper mainly deals with CoDeMo interoperability capabilities based on STEP AP203 Edition 2 standard. The aim is to show the benefit and efficiency of STEP-based application in the integration approach of CoDeMo and CAx systems. The architecture, development and application of the STEP pre-processor are described, respectively. A case study is given to illustrate the translation process of product data and to demonstrate the interest of the STEP translator.